Dynamic perennial firn aquifer on an Arctic glacier. Issue 5 (13th March 2015) - Christianson, Knut; Kohler, Jack; Alley, Richard B.; Nuth, Christopher; van Pelt, Ward J. J.
Abstract: Ice‐penetrating radar and GPS observations reveal a perennial firn aquifer (PFA) on a Svalbard ice field, similar to those recently discovered in southeastern Greenland. A bright, widespread radar reflector separates relatively dry and water‐saturated firn. This surface, the phreatic firn water table, is deeper beneath local surface elevation maxima, shallower in surface lows, and steeper where the surface is steep. The reflector crosscuts snow stratigraphy; we use the apparent deflection of accumulation layers due to the higher dielectric permittivity below the water table to infer that the firn pore space becomes progressively more saturated as depth increases. Our observations indicate that PFAs respond rapidly (subannually) to surface forcing, and are capable of providing significant input to the englacial hydrology system. Key Points: We discovered a perennial firn aquifer on an Arctic glacier The firn aquifer becomes more water saturated with increasing depth Depth to firn water table varies by several meters in response to surface melt